Frequent house invasion of Trypanosoma cruzi-infected triatomines in a suburban area of Brazil. - Gilmar Ribeiro; Rodrigo Gurgel-Gonçalves; Renato Barbosa Reis; Carlos Gustavo Silva Dos Santos; Alekhine Amorim; Sônia Gumes Andrade; Mitermayer G Reis (Public Library of Science (PLoS), 2015)
BACKGROUND:The demographic transition of populations from rural areas to large urban centers often results in a disordered occupation of forest remnants and increased economic pressure to develop high-income buildings in these areas. Ecological and socioeconomic factors associated with these urban transitions create conditions for the potential transmission of infectious diseases, which was demonstrated for Chagas disease. METHODOLOGY/PRINCIPAL FINDINGS:We analyzed 930 triatomines, mainly Triatoma tibiamaculata, collected in artificial and sylvatic environments (forests near houses) of a suburban area of the city of Salvador, Bahia State, Brazil between 2007 and 2011. Most triatomines were captured at peridomiciles. Adult bugs predominated in all studied environments, and nymphs were scarce inside houses. Molecular analyses of a randomly selected sub-sample (n=212) of triatomines showed Trypanosoma cruzi infection rates of 65%, 50% and 56% in intradomestic, peridomestic and sylvatic environments, respectively. We detected the T. cruzi lineages I and II and mixed infections. We also showed that T. tibiamaculata fed on blood from birds (50%), marsupials (38%), ruminants (7%) and rodents (5%). The probability of T. cruzi infection was higher in triatomines that fed on marsupial blood (odds ratio (OR) = 1.95, 95% confidence interval (CI) = 1.22-3.11). Moreover, we observed a protective effect against infection in bugs that fed on bird blood (OR = 0.43, 95% CI = 0.30-0.73). CONCLUSIONS/SIGNIFICANCE:The frequent invasion of houses by infected triatomines indicates a potential risk of T. cruzi transmission to inhabitants in this area. Our results reinforce that continuous epidemiological surveillance should be performed in areas where domestic transmission is controlled but enzootic transmission persists.